Isolation and Evaluation of Rhizosphere Actinomycetes With Potential Application for Biocontrolling Fusarium Wilt of Banana Caused by Fusarium oxysporum f. sp. cubense Tropical Race 4 - Zhang, Lu; Zhang, Huixi; Huang, Yating; Peng, Jun; Xie, Jianghui; Wang, Wei (Frontiers in Microbiology, 2021)
Fusarium wilt of banana caused by Fusarium oxysporum f. sp. cubense tropical race 4 (TR4) is globally one of the most destructive soil-borne fungal diseases. Biological control using environmental microorganisms is considered as an alternative and sustainable strategy. Actinomycetes have a potential for the explore of biocontrol agents due to the production of diverse metabolites. The isolation and identification of high efficiency and broad-spectrum antagonistic actinomycetes are the key for the application of biocontrol agents. In the present study, sixty actinomycetes were obtained from rhizosphere soil of Machilus pingii in the primitive ecological natural reserve of Hainan province, China. Seventeen isolates and their extracts exhibited significantly antifungal activity against F. oxysporum TR4. Especially, strain BITDG-11 with the strongest inhibition ability had a broad-spectrum antifungal activity. Assay of its physiological and biochemical profiles showed that strain BITDG-11 had the ability to produce IAA and siderophores and had a positive response to gelatin liquefaction and nitrate reduction. Enzyme activities of chitinase, β-1,3-glucanase, lipase and urease were also detected. Average nucleotide identity (ANI) calculated by comparing with the standard strain genome of Streptomyces albospinus JCM3399 was 86.55% below the novel species threshold, suggesting that the strain could be a novel species. In addition, Streptomyces BITDG-11 obviously reduced the disease index of banana plantlets and promoted the plant growth at 45 days post inoculation (dpi). The higher and lasting expression levels of defense genes and activities of antioxidant enzymes were induced in the roots of banana. Genome sequencing revealed that Streptomyces BITDG-11 chromosome contained large numbers of conserved biosynthesis gene clusters encoding terpenes, non- ribosomal peptides, polyketides, siderophores and ectoines. Fifteen bioactive secondary metabolites were further identified from Streptomyces BITDG-11 extract by Gas Chromatography-Mass Spectrometry (GC-MS). Dibutyl phthalate demonstrating a strong antifungal activity was the major compound with the highest peak area. Hence, Streptomyces sp. BITDG-11 has a great potential to become an essential constituent of modern agricultural practice as biofertilizers and biocontrol agents.